After Neoliberalism? Interregnum, Polycrisis and the Principle of Expansive Democratisation - Francesco Laruffa; Dieter Plehwe (Global Society, 2026)
In this paper, we contribute to the debate on the end of neoliberalism and on possible alternatives to the latter. We start by clarifying the relationship between neoliberalism, globalisation and the state as well as between neoliberalism, “populism”, and far-right conservatism. We argue that, despite important political-economic changes, we are still in an “interregnum”, whereby neoliberalism is increasingly challenged and dysfunctional but still dominant. Moreover, neoliberalism is mutating, as it is becoming mixed with stronger doses of nationalism and populist authoritarianism. However, the hegemonic crisis also opens the way to counterhegemonic projects. Building on Polanyi, we elaborate an analytical framework centred on the principle of expansive democratisation for distinguishing between political initiatives that aim to reinforce neoliberal hegemony and between reactionary and progressive counterhegemonic projects. We argue that building emancipatory alternatives to neoliberalism requires revitalising the critique of capitalism, fighting for global social-ecological justice.
Keywords: 300; Democratisation; global justice; neoliberalism; progressive social change; social-ecological transformation